Where is My Name? – Contemporary Funeral Posters as an Arena of Contestation and (Re)negotiation of Chiefly Relations Among the Ewe of Ghana and Togo. (9th March 2018) - Adotey, Edem
Abstract: In Ghana and other regions of West Africa a funeral poster is an important part of funerary ritual. Examining two funeral posters – one about omission and the other about inclusion of names – printed to commemorate two chiefs in two Ewe communities in Ghana and Togo, this article shows funeral posters as arenas of contestation, negotiation, affirmation, and elaboration of beliefs and conflicting views. The article argues that funeral posters are written with a local audience in mind, which means that they are a very useful source for historical enquiry about how people address the subjects of kinship and relationships among chiefs. Résumé: Au Ghana comme dans d'autres régions d'Afrique de l'ouest, les affiches funéraires sont une partie importante du rituel funéraire. En se penchant sur deux affiches funéraires – une sur l'omission et l'autre sur l'inclusion des noms – imprimées pour commémorer deux chefs de deux communautés éwé au Ghana et au Togo, cet article montre que les affiches funéraires sont des scènes de compétition, de négociation, d'affirmation et d'élaboration de croyances et de vues contradictoires. L'article soutient que les affiches funéraires sont écrites en pensant à un public local, ce qui signifie qu'elles sont une source très utile pour la recherche historique sur la façon dont les gens adressent les thèmes de la parenté et des relations entre chefs.